Absolute quantum yields and proof of proton and nonproton transient release and uptake in photoexcited bacteriorhodopsin. - Marinetti, T (1983)
Using a sensitive differential ac conductance apparatus, we have measured transient ion movements in and the heating of bacteriorhodopsin suspensions after a light flash. The signal from the heating serves as an internal calibration of the absorbed photons and therefore the method gives the absolute quantum yield (phi) from a single measurement. At pH 4, H+ uptake precedes release, with phi = 0.4. By varying the buffer composition, we can prove that this signal is due to protons. At pH 8, however, the transient conductance increase is virtually independent of the buffer composition, showing that ions other than H+ are first released and then taken up by the purple membrane. If these ions are typical monovalent cations such as Na+ (lambda = 50 ohm-1 X cm2 X equiv-1), this process has a quantum yield of 2 or more at high salt concentrations.